Gravity Research on Plants: Use of Single-Cell Experimental Models - Chebli, Youssef; Geitmann, Anja (Frontiers in Plant Science, 2011)
Future space missions and implementation of permanent bases on Moon and Mars will greatly depend on the availability of ambient air and sustainable food supply. Therefore, understanding the effects of altered gravity conditions on plant metabolism and growth is vital for space missions and extra-terrestrial human existence. In this mini-review we summarize how plant cells are thought to perceive changes in magnitude and orientation of the gravity vector. The particular advantages of several single celled model systems for gravity research are explored and an overview over recent advancements and potential use of these systems is provided.